2021
DOI: 10.3390/ijms22073360
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Chemesthesis and Taste: Role of TRPA1 and TRPV1

Abstract: In addition to the sense of taste and olfaction, chemesthesis, the sensation of irritation, pungency, cooling, warmth, or burning elicited by spices and herbs, plays a central role in food consumption. Many plant-derived molecules demonstrate their chemesthetic properties via the opening of transient receptor potential ankyrin 1 (TRPA1) and transient receptor potential vanilloid 1 (TRPV1) channels. TRPA1 and TRPV1 are structurally related thermosensitive cation channels and are often co-expressed in sensory ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 123 publications
0
22
0
Order By: Relevance
“…However, considering the present ancillary experiments with capsaicin stimulation on the cheek, such attentional effects do not seem to be very strong. Taken together, the effect of taste sensitivity enhancement by low concentration of capsaicin could conceivably involve both peripheral and central neural interactions (Rhyu et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, considering the present ancillary experiments with capsaicin stimulation on the cheek, such attentional effects do not seem to be very strong. Taken together, the effect of taste sensitivity enhancement by low concentration of capsaicin could conceivably involve both peripheral and central neural interactions (Rhyu et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While some studies provided evidence of a taste-specific activation pattern of neurons [ 51 , 52 ], other studies have shown otherwise [ 53 , 54 , 55 , 56 , 57 ]. One explanation for the present findings—that only bitter taste disrupted spatial discrimination of piperine-evoked burning sensations—relates to the ability of chemesthetic stimuli to induce bitter taste in some individuals, which might have increased the difficulty of the spatial discrimination task in terms of perceptual similarity [ 15 , 47 , 48 , 49 , 50 ]. Based on this hypothesis, one might reasonably suggest that the qualitative similarity between bitter and burning sensations is most pronounced when using weakly concentrated bitter solutions, since studies have shown that capsaicin-evoked burning sensations were mainly perceived as weakly bitter.…”
Section: Discussionmentioning
confidence: 95%
“…It is not yet possible to fully explain the qualitative similarity between burning and bitter sensations. Regarding central gustatory pathways involved in multisensory processing of gustatory and somatosensory information, previous work suggested that the gustatory cortex plays a major role in the multisensory integration of olfactory, gustatory, and somatosensory information during eating and drinking [ 46 , 47 , 48 , 49 , 50 ]. Interestingly, there is an ongoing debate about whether single taste qualities are spatially organized within the mammalian primary taste cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Irritants inhaled into the nostril often induce apnea, bradycardia, vasoconstriction, and avoidance behaviors, which also suggest the role of chemesthesis in protection. Recent studies, however, have suggested that chemical sensing by TRP channels is also involved in the sense of taste [259,260] and smell [261]. These multiple roles of chemesthesis are maybe due to the fact that TRP channels are expressed in various types of cells in the oronasal cavity.…”
Section: The Chemesthesismentioning
confidence: 99%
“…Activation of the olfactory sensory neurons can occur from the TRP channel instead of olfactory receptors [261] and a classic study by Doty et al (1978) reported that most odorants evoked some sensation in anosmic subjects [265]. Studies have also shown there are also interactions between the olfactory sense and trigeminal activation [266,267] and the sense of taste and trigeminal activation [260]. Many of the chemical compounds that enter the oronasal cavity activate the TRP channels in addition to activating the olfactory receptors and/or taste cells, affecting the quality of the sense or causing the sense by themselves.…”
Section: The Chemesthesismentioning
confidence: 99%